Tennis Shoe Outsole Temperature Changes During Hard Court Sliding and Their Effects on Friction Behaviour. (2015) - Ura, Daniel; Conway, Jacob; Booth, Jamie; Carré, Matt. J.
Abstract: Tennis is a sport played around the world on a variety of surfaces like grass, clay and hard courts. The types of surface and the surface properties influence the movements that are used by players. On hard courts, players have recently increased their tendency to perform sliding movements, possibly to reposition faster and be ready for the next shot. In order to enhance player's performance and reduce injury risk, there is a need to understand the tribological mechanisms occurring at the shoe-surface contact. The present study has developed an effective method to accurately measure temperature changes throughout a sliding movement. Friction and temperature measurements of a commercial tennis shoe outsole were measured during simulated sliding over hard court surfaces. Results indicated how the temperature changed during and after a slide. Additionally, it was found that the temperature of the shoe sole is significantly affected by the vertical load applied, and this varies depending on the shoe location tested. It was also found an inconsistent effect of surface roughness under a range of vertical loads tested. For multiple sliding tests during a rally, the shoe will increase temperature incrementally for each new slide, which could result in large changes in friction behaviour during a slide. The findings from this study could have important implications for the sport of tennis, both in terms of performance and injury-risk.